2023
DOI: 10.3390/microorganisms11051305
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and B Cell Receptor (BCR) Inhibitors for the Treatment of Chronic Lymphocytic Leukemia: Is Biodiversity Correlated with Clinical Response or Immune-Related Adverse Event Occurrence? A Cross-Sectional Study

Abstract: Several studies have strengthened the link between the gut microbiota (GM) and the response to immunotherapy in patients with tumors, highlighting the potential role of GM as a biomarker of response. Targeted therapies including B-cell receptor (BCR) inhibitors (BCRi) represent the newest approach to the treatment of chronic lymphocytic leukemia (CLL); however, not all patients achieve a satisfactory response, and immune-related adverse events (irAEs) can also impact the efficacy. The aim of the study was to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…For instance, antibiotic treatment that down-regulates the gut microbiota can restore the anti-leukemia efficacy of APO866 (ElMokh et al, 2022). Using B-cell receptor inhibitors (BCRi) as targeted therapy can up-regulate the Bacteroidia levels in CLL patients (Zuccaro et al, 2023). This also seems to underscore the association between the gut microbiota and leukemia.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, antibiotic treatment that down-regulates the gut microbiota can restore the anti-leukemia efficacy of APO866 (ElMokh et al, 2022). Using B-cell receptor inhibitors (BCRi) as targeted therapy can up-regulate the Bacteroidia levels in CLL patients (Zuccaro et al, 2023). This also seems to underscore the association between the gut microbiota and leukemia.…”
Section: Discussionmentioning
confidence: 96%
“…Another study found that the gut microbiota of CLL patients treated with B cell receptor (BCR) inhibitors who met the clinical response criteria had a higher number of bacteria from the class Bacteroidia and the order Bacteroidales , they also noted an inversion in the Firmicutes and Bacteroidetes ratio in the patients who undergo adverse effects such as diarrhea. 36 …”
Section: Gut Microbiota and Hematological Malignanciesmentioning
confidence: 99%